Fishing for a Solution Canada's Fisheries Relations with the European Union, 1977-2013 - Applebaum, Bob; Wiseman, Earl; Barry, Donald (Beyond Boundaries, 2014)
Fishing for a Solution provides a detailed, policy-based account of the development of Canada's fisheries relations with the European Union. It covers over 35 years of this contentious international relationship, from the extension of Canada's fisheries jurisdiction to 200 miles in 1977 and the creation of the Northwest Atlantic Fisheries Organization (NAFO) two years later, to the development of a proposed new NAFO Convention in 2007, which awaits formal approval. Based on the experience of participants from inside the deliberations and negotiations, the book explores the impact of Canada's internal politics on international fisheries negotiations. For anyone interested in the workings of Canadian foreign policy, resource policy or in the complexities of managing international relations, it offers a unique account of the development of Canada-EU fisheries relations, blending the academic perspective of a long-time student of those relations with the insights of two former senior public servants who led the international affairs directorate of Canada's Department of Fisheries and Oceans.